Green Light Photo Selective Vaporization of the Prostate vs. Transurethral Resection of Prostate for Benign Prostatic Hyperplasia - Mahboub Ahari, Alireza; Sadeghi Ghyassi, Fatemeh; Yousefi, Mahmoud; Amjadi, Mohsen; Mostafaie, Ali (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Green light photo selective vaporization of the prostate (PVP) is a minimally invasive method of treatment for clinical benign prostatic hyperplasia with fewer side effects. The aim of this study is to evaluate the safety, effectiveness and cost analysis of PVP compared with transurethral resection of prostate. METHODS: A systematic search was done in Cochrane, TRIP database, MEDLINE, NHS EED, NIHR HTA, CRD, Health star database, Pro Quest, Psycoinfo and Google Scholar to find randomized control trials, systematic reviews and HTA reports. The searched keywords were Green light laser (PVP or KTP) and prostate. The cost analysis was done by the perspective of society and providers. RESULTS: Complication rate in 12 included evidences ranged from 0-9.3%. The complication rate of TUR-P (Transurethral Resection of Prostate) was more than PVP. Changing in flow rate reducing residual urine, improving patients’ symptoms and QOL (Quality of life), and operative outcome length of operation varied from no significant to significant differences in favor of TURP. Unit cost in both social and provider view was significantly high in PVP in comparison with TURP. Increasing the number of patients did not change the cost analysis. CONCLUSION: PVP is a safe method for treatment of clinical BPH, but there is a lack of evidence for the evaluation of effectiveness. Overall, the unit cost for PVP was significantly more than TURP; for this reason this method could not be conducted in very wide indications, because of high cost.